The Relationship Between Risk and Resilience, Racial Microaggression, Ethnic Identity, and Well-Being in Young Adulthood - Forrest-Bank, Shandra S. (2012)
Young adulthood is the developmental period characterized by the transition from adolescence to the roles and responsibilities of adulthood. While most young adults experience positive growth and accomplishments, many others struggle, especially those with disadvantaged childhoods who lack financial, social, and emotional resources. Substance abuse, crime, educational failure, unemployment, and mental health problems are common among young adults. Unfortunately, many of these problems occur at disproportionately high rates for young people of color. Considerable knowledge of the child and adolescent risk and protective factors that contribute to the onset of problem behavior or to well-being during adolescence has been developed. However, evidence from longitudinal studies spanning childhood, adolescence, and adulthood indicates that little is known about the influence of early risk and protective factors on the onset, remittance, or persistence of problem behavior or well-being during adulthood. In addition, few studies have examined the effects of racial discrimination and ethnic identity on problem behavior and well-being. This study examined the relationship between child and adolescent risk and protective factors for problem behavior, perceived racial and ethnic microaggression, ethnic identity, and the young adult outcomes of self-efficacy, substance abuse, and criminal intention. Data were collected from a randomly selected sample of college students (N=486; Mean Age=24) attending an urban college in Denver, Colorado. Findings from structural equation modeling revealed that the early onset of problem behavior was significantly related to both substance abuse and criminal intentions during young adulthood. Childhood school engagement was positively related to college self-efficacy, and negatively related to criminal intentions. Perceived racial microaggression and ethic identify were significantly related to academic self-efficacy. One-way analysis of variance tests revealed significant differences in mean scores on the microaggression and ethnic identity scales between racial and ethnic groups. All nonwhite groups reported significantly higher levels of microaggression than their white peers. Mean cognitive ethnic identity scores were significantly higher for black and Latino/Hispanic subjects compared to Asian and white participants. The implications of these findings for practice, policy, and research with young adult populations are identified